A Framework for Modeling Non-Functional Requirements for Business-Critical Systems (International Journal of Innovative Research in Computer Science & Technology, 2023)
Proper definition and implementation of  NFRs is critical. In case they are Over-specify, then the  solution may be too costly to be viable; in case they are  underspecified or underachieve them, the system will be  inadequate for its intended use. An adaptive and  incremental approach to exploring, defining, and  implementing NFRs is vital for the successful delivering of  NFRs. NFRs are not product backlog items. The constraints  on development that limit degree of design freedom while  building system. These constraints are articulated in the  acceptance criteria for multiple product backlog items. For  e.g., SAML-based Single Sign-on - SSO is a requirement  for the product. SSO is a functional requirement, while  SAML is the constraint. In that sense, any backlog item  building sign-on functionality would reference the SAML  constraint in its acceptance criteria. The sections that follow  describe the phases of NFR journey from discovery to  deployment for a large complex business critical systems  including the NFR modelling framework.
Keywords: NFR-Non-Functional Requirements; NFR Framework; NFR Modelling; NFR Methodology